2006
DOI: 10.1007/s00586-006-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

Results of brace treatment of adolescent idiopathic scoliosis in boys compared with girls: a retrospective study of 102 patients treated with the Boston brace

Abstract: The aim of the study was to compare the results of brace treatment of adolescent idiopathic scoliosis (AIS) in male patients with matched female patients and to assess the effectiveness of bracing of boys in AIS and to discuss the results with published data. Between 1987 and 1995, 51 consecutive male patients with AIS were treated with the Boston brace. The patients were advised to wear the brace 23 h/day. The medical records of all patients were reviewed. Cobb angles and Risser signs were measured before bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 21 publications
4
43
0
1
Order By: Relevance
“…Similarly, 55% of curves measuring greater than 30°at brace prescription progressed to surgery or greater than 50°. Yrjonen et al [59] supported these results finding 35% of braced males were noncompliant. However, although compliant males progressed greater than 5°10% more frequently than the females (21%), they concluded brace treatment for idiopathic scoliosis was beneficial for both genders.…”
Section: Bracing Difficultiesmentioning
confidence: 77%
See 1 more Smart Citation
“…Similarly, 55% of curves measuring greater than 30°at brace prescription progressed to surgery or greater than 50°. Yrjonen et al [59] supported these results finding 35% of braced males were noncompliant. However, although compliant males progressed greater than 5°10% more frequently than the females (21%), they concluded brace treatment for idiopathic scoliosis was beneficial for both genders.…”
Section: Bracing Difficultiesmentioning
confidence: 77%
“…It is these characteristics that cause bracing in the overweight patient to be ineffective and lead to increased curve progression compared with patients who are not overweight [31,35]. Brace compliance was potentially responsible for the disparity of success between males and females treated with bracing [22,59] and may explain the similar results of noncompliant patients with the natural history. Numerous studies have demonstrated compliant brace wear leads to successful results, yet much of the data, as acknowledged by the authors, is subjective based on incomplete assessments of compliance such as office notes, questionnaires, or phone or office interviews [22,30,34,58].…”
Section: Bracing Difficultiesmentioning
confidence: 99%
“…The duration for which the brace was to be worn was adjusted during each follow-up based on the Risser sign, the menarchal status in females, and whether the Cobb angle was stable compared with earlier data. If the curve remained stable (i.e., the change in the Cobb angle of the main curve was less than 5°) [15,20], the daily wearing time of the brace would not change for the first 6 months; rather, it would be shortened to 18 h per day for the next 6 months. The patients' scoliosis was considered to be worse if the Cobb angle increased by more than 6° [15,20].…”
Section: Methodsmentioning
confidence: 99%
“…If the curve remained stable (i.e., the change in the Cobb angle of the main curve was less than 5°) [15,20], the daily wearing time of the brace would not change for the first 6 months; rather, it would be shortened to 18 h per day for the next 6 months. The patients' scoliosis was considered to be worse if the Cobb angle increased by more than 6° [15,20]. If this occurred, then daily bracing time was maintained at 22 h per day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation